Kinetic characterization of brush border myosin-I ATPase - Jontes, James D. (The National Academy of Sciences of the USA, 1997)
Brush border myosin-I (BBM-I) is a single-headed unconventional myosin found in the microvilli of intestinal epithelial cells. We used stopped-flow kinetic analysis to measure the rate and equilibrium constants for several steps in the BBM-I ATPase cycle. We determined the rates for ATP binding to BBM-I and brush border actomyosin-I (actoBBM-I), the rate of actoBBM-I dissociation by ATP, and the rates for the steps in ADP dissociation from actoBBM-I. The rate and equilibrium constants for several of the steps in the actoBBM-I ATPase are significantly different from those of other members of the myosin superfamily. Most notably, dissociation of the actoBBM-I complex by ATP and release of ADP from actoBBM-I are both very slow. The slow rates of these steps may play a role in lengthening the time spent in force-generating states and in limiting the maximal rate of BBM-I motility. In addition, release of ADP from the actoBBM-I complex occurs in at least two steps. This study provides evidence for a member of the myosin superfamily with markedly divergent kinetic behavior.